EXPLORING THE COVID-19 PANDEMIC IMPACTS ON MALAYSIAN RURAL SMALLHOLDER FARMERS IN KUCHING, SARAWAK - Cheah, Whye Lian; Myat, Su Bo; Angel Wong, Yi Wen; Nur Fatini Amni, Mohd Fauzi; Mohammad Shahrulnizam, Hatity; Azyan Hannany, Aseri; Yeo, Zhi Sheng (Universiti Malaya, 2024)
The current study aims to explore the Coronovirus 2019 (COVID-19) pandemic impacts on Malaysian rural smallholder farmers in Kuching, Sarawak. Purposive sampling was employed and a qualitative descriptive approach was adopted. This study centred on a group of rural smallholder farmers actively participating in a food assistance programme for impoverished urban communities in Kuching. The farmers played a pivotal role in supplying vegetables and crops for the food assistance programme. The data were collected through semi-structured individual in-depth interviews. A thematic analysis was conducted, which revealed several major themes, namely the challenges encountered by smallholder farmers during the pandemic, the responses to the crisis, the recovery strategies, and subsequent plans. The current study not only enriched the understanding of the challenges encountered by rural smallholder farmers but also determined the underlying issues. The insights could serve as a foundation for developing specific solutions by relevant authorities to address rural smallholder farmers’ respective needs.